2018
DOI: 10.1007/s10140-018-1598-7
|View full text |Cite
|
Sign up to set email alerts
|

Are all urgent nephrostomies that urgent?

Abstract: A large percentage (50%) of PCN cases performed after-hours could have been performed during daytime hours instead due to the absence of infection. This would be in line with the practices of some centers that consider an infected obstructed kidney as the only absolute indication for emergent decompression overnight. The study also demonstrates that the absence of a SIRS in a patient with urinary tract obstruction correlates well with a negative urine culture result from the nephrostomy specimen which has a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The bi-laterality of OU among patients who are candidates for PCN is variable in most studies, ranging from 35 to 55%. 8,9,14 Our study showed that 77 (60%) of the studied patients presented with involvement of both kidneys and all of them were diagnosed with AKI, which is explained by the finding that >80% of our patients had…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The bi-laterality of OU among patients who are candidates for PCN is variable in most studies, ranging from 35 to 55%. 8,9,14 Our study showed that 77 (60%) of the studied patients presented with involvement of both kidneys and all of them were diagnosed with AKI, which is explained by the finding that >80% of our patients had…”
Section: Discussionmentioning
confidence: 66%
“…This finding supports the observation stated by various studies in which post-obstructive AKI accounts for 72-90% of the indications for PCN and has a higher probability of a successful outcome; this can be explained by the usual presence of marked hydronephrosis in such patients. 2,9,10 PCN is a kidney-saving and, for that matter, life-saving emergency procedure with a high success rate. 11,21 In the year 1974, Pedersen first described ultrasound-guided placement of PCN tube into an obstructed kidney and reported a success rate of 75%.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with sepsis due to pyelonephritis, imaging studies become important for detecting conditions that must be corrected in order to prevent worse outcomes [3]. Obstruction in the urinary tract can be due to calculi, tumors, strictures, or anatomical abnormalities, which invariably will lead to hydronephrosis; an infected obstructive kidney is considered an indication for urgent urologic evaluation because mortality rates associated with septic shock could approach 40% [4]. Studies have shown a sensitivity of point-of-care ultrasound (POCUS) of 72-83.3% [1].…”
Section: Introductionmentioning
confidence: 99%